Fearful symmetry : India-Pakistan crises in the shadow of nuclear weapons - Ganguly, Sumit (University of Washington Press, 2005)
With the nuclearisation of the Indian sub-continent, Indo-Pakistani crises have acquired a deadly significance. The authors examine six crises of the past two decades and the role that nuclear weapons and the security dynamics of the United States in theregion have played in averting a major conflict.